From CAA to CFD - Rinie A. D. Akkermans and Paul Bernicke and Roland Ewert and Jürgen Dierke (Proceedings in applied mathematics and mechanics, 2016)
In this contribution, an application of a computational aeroacoustic code as a hybrid Zonal LES tool is presented. The here used hybrid approach is based on a novel implementation of the Non-Linear Perturbation Equations extended with fluctuating viscous terms, denoted as “Overset” since a perturbation analysis is performed on top of a background flow. The extension to LES is demonstrated with isotropic decaying turbulence, where the expected temporal decay and scaling of the reference DNS data is recovered with the LES employing a classical Smagorinsky model. Furthermore, a conceptual approach is presented that describes the investigation of sound sources with application to trailing-edge noise.